The Effect of Performance Measurement EVA and ROE on Islamic Stock Price - Adib Adib; Hartomi Maulana (University of Darussalam Gontor, 2021)
This research aims to identify the effect of performance measurement on Islamic Stock Price. Specifically, the research obtained the goals to measure performance of the company by their stock which are listed in Sharia Securities Issues (DES). This research uses secondary data derived from the annual report published in website of Financial Authority of Indonesia on www.idx.co.id. This research will take 86 annual report which are come from 43 companies in 2 years. EVA and ROE used as independent variable while stock price as dependent variable. This research uses classical assumption as the research method. The result from this research shows that EVA and ROE simultaneously have significant effect on the stock price. Specifically each independent variable has also significant effect on the stock price. The result indicated that if EVA and ROE increased, stock price will increase because net income good performance of the company. One of the benefits of this research for investor EVA and ROE can be a consideration decision to invest in the stock.Key words : Economic Value Added (EVA), Return on Equity (ROE), Stock Price, List of Sharia Securities Issues, Financial Authority